ANALISIS PEMBONCENGAN REPUTASI (PASSING OFF) DALAM ETIKA BISNIS ISLAM (Studi Kasus Penggunaan Merek Elizabeth pada Pedagang Es Cendol Di Kota Bandung) - Syahidah, Khansa Hanifah; Fitri, Atiyah (Prodi Manajemen Bisnis Syariah, 2024)
This study aims to find out how ice cendol sellers who use the Elizabeth brand in the city of Bandung are viewed from Islamic business ethics. The type of research used is qualitative research with a descriptive analysis approach. The data collection techniques using interview techniques, observation and documentation. The data analysis technique used is descriptive qualitative method. The results of this study are about Es Cendol traders who use the Elizabeth brand in the city of Bandung, namely from a consumer perspective, many consumers like Es Cendol Elizabeth, which is sold by street vendors because it is cheap and easy to obtain, from the point of view of Es Cendol traders who use the Elizabeth brand, it is very benefit because many consumers like it, and it becomes a business opportunity for Es Cendol traders to use the Elizabeth brand so as to gain both short and long term benefits. However, the act of using the Elizabeth brand has violated copyright regulations in Indonesia. The traders have carried out the reputation (passing off) of famous brands, in terms of Islamic business ethics this action is included in ghasy (manipulation) or Khida (fraud). Merchants have applied the principles of building good and trustworthy business relationships with consumers, seen by their friendliness in serving buyers and completing orders well, and they sell at quite cheap prices, so they have many customers. however, some principles have not been applied optimally due to the lack of knowledge about true and good muamalah.